2014
DOI: 10.3329/bmj.v43i1.21368
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors of multidrug resistant tuberculosis with emphasis on serum zinc

Abstract: Multi-drug resistant tuberculosis (MDR-TB) is a form of TB resistant to isoniazid and rifampicin and considered as a major threat to TB control worldwide. Limited data are available regarding risk factors and serum zinc status of MDR-TB in Bangladesh. Tuberculosis is a disease which blocks a key part of the body’s immune defense. As zinc deficiency causes immune suppression, we assume that it may play a role in the development of MDR-TB. So, this study was carried out to evaluate and assess the serum zinc leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
4
0
4
Order By: Relevance
“…Amin et al (2009) conducted a study in Bangladesh, which showed that the highest proportion of MDR-TB cases (61.2%) were involved in occupations like agriculture, production and transport but no significant difference was obtained in income level between cases and controls. In other study done by Baghaei et al (2009) and Barman et al (2014) family size showed significant association with MDR-TB as in our study. Individual staying in a crowded living condition are more vulnerable to develop MDR-TB.…”
Section: Risk Factors Associated With the Development Of Mdr-tbsupporting
confidence: 66%
“…Amin et al (2009) conducted a study in Bangladesh, which showed that the highest proportion of MDR-TB cases (61.2%) were involved in occupations like agriculture, production and transport but no significant difference was obtained in income level between cases and controls. In other study done by Baghaei et al (2009) and Barman et al (2014) family size showed significant association with MDR-TB as in our study. Individual staying in a crowded living condition are more vulnerable to develop MDR-TB.…”
Section: Risk Factors Associated With the Development Of Mdr-tbsupporting
confidence: 66%
“…Bakteri M.tb merupakan bakteri patogen pada paru, namun dapat menyebabkan penyakit di hampir seluruh bagian tubuh. [1][2][3][4] Tuberkulosis menjadi penyebab utama morbiditas dan mortalitas di negara-negara yang berpendapatan rendah dan berpenghasilan menengah. 5 Penderita tuberkulosis paru di dunia tahun 2014 sebanyak ±9,6 juta kasus dan tahun 2015 sebanyak ±10,4 juta kasus.…”
Section: Pendahuluanunclassified
“…6,7 Penderita tuberkulosis paru di Indonesia pada tahun 2015 sebanyak 330.910 kasus dan meningkat pada tahun 2016 menjadi 351.893 kasus. Kasus TB paru di Indonesia didominasi oleh provinsi dengan jumlah penduduk besar yaitu Provinsi Jawa 1 10 Jumlah penderita MDR-TB di dunia meningkat dari tahun 2014 sampai 2015 yaitu dari 480.000 kasus menjadi 580.000 kasus, sedangkan di Indonesia juga terjadi peningkatan dari 9.399 kasus pada tahun 2014 menjadi 15.380 kasus pada tahun 2015. 7,11 Penyakit menular kronis ditandai dengan peningkatan respon kekebalan tubuh yaitu proses yang menyebabkan kerusakan sel.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations